BANKING RESTRUCTURING PROGRAM IN VARIOUS COUNTRIES IN THE WORLD - Zahara, Zahara; Simahatie, Mai; Rahmi, Rahmi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study is to see how the restructuring programs carried out in various countries and their impact on the economy in their country. As is well known Non-Performing Loans (NPLs) that are too high cannot be tolerated because they can cause banks to become unhealthy and can indirectly adversely affect the economy of a country. So it is important to examine how developed countries make restructuring programs and the extent to which these programs can have an impact on their country's economy. This research method is qualitative descriptive with the type of library research, literature collection is carried out using the application of Harzing's Publish or Persih Web Dimensions, Google Scholer and so on. The literature collection period is the last 10 years, namely 2012-2022, then the data is processed using Vosviewer and described. From the literature review obtained, the restructuring was carried out as an effort to save troubled banks. Countries in the world such as Indonesia, Thailand, Malaysia, South Korea, China, Switzerland and the UK, the European Union, Spain, Ireland, Italy, Greece, have their own and different ways of rescuing troubled banks in their countries, starting from closing down troubled banks, selling bankrupt banks to forming a special agency for handling troubled banks.